High time resolution records of sulfur and insoluble particle concentrations from five ice cores from Greenland and one from Antarctica between 1530 and 1710 CE and inferred volcanic contributions - Michael Sigl; Joseph R McConnell; Nathan J Chellman; Imogen Gabriel (PANGAEA, 2025)
We report high time resolution (i.e. close to monthly) non-sea-salt sulfur concentrations from six ice cores including WDC (Antarctica) and Summit2015, Summit2023, NEEM-2011-S1, TUNU2013, and B19 (Greenland) analyzed using inductively coupled plasma mass spectrometry (ICPMS) at the Desert Research Institute. For Summit 2015, Summit 2023, B19 and TUNU2013 we also provide mass concentration records of insoluble particles (5-10 μm) using an inline Abakus® laser particle counter. Additional details about the ice-core sites and analytical procedures are provided in the Supporting Data of Gabriel et al., (submitted) and in the references below citing the original publications. From three monthly resolved records (WDC, Summit15, NEEM-2011-S1) we infer a mean annual cycle of background sulfur concentrations using the median across the same months in a volcanically quiescent time (1530-1580 CE) while omitting months influenced by smaller volcanic eruptions. We then subtract this mean background cycle from the total sulfur concentrations to derive volcanic sulfur concentrations (ng/g) and volcanic sulfate depositions rates (kg km-2 month-1) at nominal monthly resolution. These records are used alongside ice-core crypto-tephra to characterize volcanic eruption sources and to disentangle individual volcanic sulfur depositions on the polar ice sheets arising from temporal clusters of volcanic eruptions such as in the 1590s, 1600s, 1640s, 1660s and 1690s CE.